Evaluation of glide inductance loop detectors for volume counts - Min Min Naing. (2008)
The performance of the GLIDE inductance loop detectors was evaluated to study their reliability for counting vehicles. Data were collected at eight approached of six junctions. Quarterly-hour traffic counts were collected by two methods, one as provided by the GLIDE inductance loops and the other by manual counting from video recordings.